Assessing an exploratory digital environment for learning about southern African pre-colonial urbanism in space and time : a case study for Seoke, the capital of the Bangwaketse - Coetzee, Serena Martha (University of Pretoria, 2022)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2022.